Zachowania prospołeczne i inteligencja emocjonalna studentek – przyszłych nauczycielek edukacji wczesnoszkolnej - Wereszczyńska, Katarzyna (Kultura-Społeczeństwo-Edukacja, 2025)
The introductory part of the paper focuses on the relevance of the child’s social and pro-social upbringing in the family and school environment. In order to explore the pro-social and emotional potential of those who began their studies with the specialisation of early childhood education teacher, a diagnostic study was conducted. The study targeted female students of the first year of Pre-school and Early Childhood Pedagogy at the University of Opole and the Pro-social Behaviour Questionnaire (PBQ) as well as the Emotional Intelligence Questionnaire – INTE were used as research tools. The materials included in the article come from research carried out in the academic year 2024/2025; they provide data on the level of frequency of pro-social behaviours in showing help, support and involvement in volunteer activities.